Behavioral engineering: postural control by a portable operant apparatus - Azrin, N. (1968)
Recent studies suggested a general behavioral engineering approach to behavioral disorders by portable operant treatment instruments. The approach was applied to the problem of poor posture, specifically rounding of the back or slouching. An apparatus was developed that provided a warning stimulus followed by an aversive tone for the duration of slouching. Slouching was thereby punished by onset of the tone, and non-slouching was reinforced by tone termination and postponement. Twenty-five adults wore the apparatus during their normal working day during alternate periods in which the aversive tone was connected and disconnected experimentally. A miniature time-meter recorded the duration of slouching. The results showed that slouching decreased for each subject during each period in which slouching produced the aversive tone. For two subjects, a second control procedure was applied in which slouching terminated the tone. The result was an increase of slouching, demonstrating that the postural changes were controlled by the scheduled relation between the aversive tone and the response, and not by other factors such as simple response feedback. The substantial changes in posture indicate that the present procedure may prove to be an effective treatment alternative and suggests the general value of the behavioral engineering approach.